Manajemen Kurikulum Satuan Pendidikan Mu'adalah - Zarkasyi Zarkasyi; Ari Kartiko (LP3M STIT Al Urwatul Wutsqo Jombang, 2024)
The Mu'jadi Ulya Education Unit has its own curriculum which is combined with the characteristics of the Islamic Boarding School. In Aceh, one of the Islamic boarding schools that organizes the Mu'adalah Education Unit is Dayah Mesjid Raya Samalanga which has received an operating permit since 2011. The aim of the research is to analyze the curriculum management of the Mu'ilah Ulya Education Unit organized by Dayah Mesjid Raya Samalanga, both its implementation and evaluation. The research is qualitative research with a case study approach. Data collection techniques use observation, interviews and documentation. The data sources for this research are the head of the Mu'adalah Ulya Education Unit, Dayah Mesjid Raya Samalang curriculum sector, teachers who teach at the Mu'adalah Ulya Education Unit and santri. The analysis techniques used are data collection, data reduction, data presentation, drawing conclusions. The triangulation used to test the validity of the data is technique and source triangulation. The results of the research show that (1) Even though it is a Traditional Education Institution, it has been able to implement management of the Mu'ilah Education Unit Curriculum in accordance with applicable regulations. (2) One of the foundations for strengthening the curriculum building is the managerial foundation, this has been implemented well. (3) One way to maintain the quality of implementation of the Mu'ilah Education Unit curriculum is with a strict and selective teacher recruitment process. (4) Curriculum evaluation has been carried out in the form of formative and summative assessments which include the learning process carried out by the teacher and followed by the Santri